A study on remote masking - BS, Premalatha (Journal of All India Institute of Speech and Hearing)
The ph.enomenon of Remote Masking was first described by Bilger and Hirsh (1956). Reluote Maskingis a low frequency phenomenon. It consists of a threshold rise for low-frequency tone wh n the ear is expJsed to a high frequency noise band delivered at overall Spl of 80-100 dB.